Reading Without Words: Eye Movements in the Comprehension of Comic Strips. Issue 4 (15th April 2016) - Foulsham, Tom; Wybrow, Dean; Cohn, Neil
Summary: The study of attention in pictures is mostly limited to individual images. When we 'read' a visual narrative (e.g., a comic strip), the pictures have a coherent sequence, but it is not known how this affects attention. In two experiments, we eyetracked participants in order to investigate how disrupting the visual sequence of a comic strip would affect attention. Both when panels were presented one at a time (Experiment 1) and when a sequence was presented all together (Experiment 2), pictures were understood more quickly and with fewer fixations when in their original order. When order was randomised, the same pictures required more attention and additional 'regressions'. Fixation distributions also differed when the narrative was intact, showing that context affects where we look. This reveals the role of top‐down structures when we attend to pictorial information, as well as providing a springboard for applied research into attention within image sequences.Copyright © 2016 John Wiley & Sons, Ltd.